ANALISIS KONSUMSI BAHAN BAKAR PEMBANGKIT LISTRIK TENAGA DIESEL DENGAN SUBTITUSI GASIFIKASI SABUT KELAPA - Deisy Pakiti; D. Pangkerego; D. Tooy; D. Ludong (Universitas Sam Ratulangi, 2016)
ABSTRACTBiomass energy is an alternative energy that is converted from biological material derived from recently dead organisms into energy to be used as a power plant. The purpose of this study of was to analyze the energy consumption of gas produced biomass and its comprasion with diesel fuel. Alaysis was done by varying loading on diesel power plants with a substitution gas from gasification of biomass from coconut husk. Conversion of biomass energy as a source of electrical energy was obtained from the downdraft gasifer. This research uses experimental methods to analyze the consumption of diesel fuel in some electrical loading with the substitution of diesel with the coconut husk produced gasification. Electrical load variation are : 500W, 1000W, 1500W, 2000W. the results of the study with 12,34% water content show that the higher the electrical load is used, the grater the fuel used. The consumption of diesel fuel can be reduced by using biomass gasification. The diesel reduction generated at a load of 500W is 50,87, and the reduction of diesel fuel consumption of loads of 1000W, 1500W and 2000W are 48,81%, 46,98% and 44,48%. It is advisable to further simplify the process of providing raw materials which is prepared manually, due reques a hard effort to unifom the size of coconut husk. Keywords : gasification, solar fuel